Accounting trends in the modern world - Melnyk, Natalya; Trachova, Daria; Трачова, Дар'я Миколаївна; Kolesnikova, Olena; Demchuk, Olena; Демчук, Олена Миколаївна; Holub, Natalia; Голуб, Наталя Олександрівна (My University, 2020)
The purpose of the article is to determine the current directions and future trends in the development of accounting. The conclusions made on the basis of research materials, surveys, reports of reputable international and professional accounting organizations. Synthesis and analysis reveal that some trends and drivers among analyzed will be more significant (such as globalization of business and the profession; spread of digital technologies; expectations of business and professional accountants) than others (such as regulation and governance) and will, in varying degrees, affect specific accounting roles, skills, knowledge. As a result of research, was determined that modern accounting professionals move from performing technical accounting functions (hard skills) to support the companies` management and play a significant role in improving the development of society. It is established that the main thing in the strategy of accounting companies` progress (both large and SMEs) and accounting specialists will be the development of the latest technologies, soft skills, professional flexibility. It is substantiated that the change of priorities will turn the challenges facing the accounting profession into its advantages.
Keywords: accounting; trends; professional; accountant; knowledge; skills